1979
DOI: 10.1159/000232218
|View full text |Cite
|
Sign up to set email alerts
|

Allergenicity of Concanavalin A in Mice

Abstract: Concanavalin A (Con A) is a potent allergen in certain strains of mice and in particularly the H-2Kk mice, A/J, CBA/H, and C3H/He. Using a dose of 100 μg, the subcutaneous route of injection was the most effective means of inducing high, persistent titers of T cell-dependent circulating anti-Con A reagins without the addition of the classical ‘ΙgE adjuvants’, aluminium hydroxide and Bordetella pertussis vaccine. Haptenated Con A induced reagins with antihapten specificity. In the discussion, one pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1981
1981
1999
1999

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“…Recently, Mitchell & Clark demonstrated that a single injection of Con A induced anti-Con A IgE antibodies in mice without the use of adjuvants (16). Repeated subcutaneous injections of grass pollen extract or DNP-ovalbumin without adjuvant stimulated IgE responses to pollen allergens and DNP (19).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Mitchell & Clark demonstrated that a single injection of Con A induced anti-Con A IgE antibodies in mice without the use of adjuvants (16). Repeated subcutaneous injections of grass pollen extract or DNP-ovalbumin without adjuvant stimulated IgE responses to pollen allergens and DNP (19).…”
Section: Discussionmentioning
confidence: 99%
“…dubius, or are able to gain access from the intestines subsequent to damage ofthe intestinal wall by N.dubius, then severe inflammatory consequences may result from mast cell degranulation. This despite the fact that the SJL/J is a well known low IgE producer (literature cited in Lehrer et al 1975, Mitchell & Clarke 1979, Katz 1980. Perhaps the SJL/J mouse "cannot afford" to be a high IgE responder to allergens (see Section II.…”
Section: Nematospiroides Dubius: Resistance To Reinfectionmentioning
confidence: 99%
“…There was no enhancement of proliferation of the mesenteric lymph node cells with small quantities of ricin. Many substances have been described that poten tiate IgE responses in animals [12][13][14], A number of plant products have been reported to potentiate IgE responses in rodents [15,16], although not as actively as castor bean ricin [11]. The target of ricin is not known.…”
Section: Resultsmentioning
confidence: 99%